The Consequences of Leaving School Early: The Effects of Within-Year and End-of-Year Teacher Turnover - Henry, Gary T; Redding, Christopher (Education finance and policy, 2020)
Using unique administrative data from North Carolina that allow us to separate classroom teacher turnover during the school year from end-of-year turnover, we find students who lose their teacher during the school year have significantly lower test score gains (on average -7.5 percent of a standard deviation unit) than those students whose teachers stay. Moreover, the turnover of other teachers during the year lowers achievement gains, whereas end-of-year teacher turnover appears to have little effect on achievement. The harmful effects of within-year turnover cannot be explained by other extraneous shocks or the quality of departing teachers. Teachers who depart from December through April have the most harmful effects on achievement, although these vary somewhat by level of schooling and subject.